Sindicatos no Brasil: O que esperar no futuro próximo? - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Nowadays, there is a growing debate about the role of collective bargaining in Brazilian labour regulation. Nonetheless, is it possible to discuss such a role without debating the collective actors engaged in that bargaining? The answer is probably no, at least with respect to labour actors (unions), which face several problems. There are thousands of unions in Brazil, spread by every economic sector, professional branch and region of the country. At a first glance, this would seem very promising in order to foster a negotiated labour regulation. However, on average, those unions present a fragile constituency, with few workers in their social base, as well as a small affiliation among them. As a result of this frail constituency, unions gather little resources to negotiate new forms of labour regulation.
Keywords: J50; J51; J59; 330; labour regulation; collective bargaining; unions